Penentuan Jumlah, Lokasi dan Cakupan Distribusi Gudang Produk Air Minum Dalam Kemasan Jenis Gelas (Studi Kasus di PT. Dzakiya Tirta Utama) - Dyan Parardyo S; Yuniaristanto -; Bambang Suhardi (Performa: Media Ilmiah Teknik Industri, 2005)
This paper studies a facility location with single sourcing problem which simultaneously considering opening some new facilities or closing some existing facilities. This problem comes from the inefficiency of the distribution network because of its distribution process growth. One of the mainly caused is each customer zone, which consist of several demand points, served by more than one warehouses. This policy causes high delivery cost and also makes what called marketing conflict. The objectives of this problem solving is determining number, location and distribution coverage of warehouse that could minimizing total logistic cost. Total logistic cost consist of delivery cost from warehouse to customer zone, storage and operation cost at warehouse and transportation cost from plant to warehouse. The best solution is achieved using heuristic approach and optimized using integer linear programming by examining the best configuration network offering the least total logistic cost.